A new look at inflation : economic policy in the early 1970s - Cagan, Phillip; American Enterprise Institute for Public Policy Research (Washington, DC: American Enterprise Institute for Public Policy Research, 1973)
The book examines inflation and presents the diverse opinions of distinguished scholars on developments in the American economy since the institution of direct wage and price controls in August 1971.
Includes bibliographical references.
usc 21/6/18
Loans
Keywords: Inflation (Finance); Wage-price policy; Economic policy